Strategies for early metabolic disturbances in patients with an end jejunostomy or end ileostomy. Experience from a specialized Home Parenteral Nutrition (HPN) center - Ławiński, Michał; Haraszczuk, Dominika; Gradowska, Aleksandra; Kostro, Justyna Z.; Bzikowska, Agnieszka; Sobocki, Jacek (Gastroenterology Review/Przegląd Gastroenterologiczny, 2017)
Introduction : An end stoma syndrome is usually the result of an intentional surgical intervention in the course of staged treatment or a complication of surgery. These patients most frequently suffer from water and electrolyte disturbances, malnutrition syndromes caused by malabsorption of trace elements and/or vitamins, and undernutrition. Aim : To present early metabolic disturbances observed in patients with an end jejunostomy or end ileostomy syndrome on the first day of their hospitalization in a specialist Home Parenteral Nutrition (HPN) center. Material and methods : The study included 142 patients with an end stoma syndrome (76 women and 66 men), hospitalized between 2004 and 2014. Patients were divided into two main groups. Group A consisted of 90 patients with an end jejunostomy and group B consisted of 52 patients with an end ileostomy. Results : After comparing the patients with an end jejunostomy vs. those with an end ileostomy, significant differences were found as regards pH (7.34 vs. 7.39, p = 0.043) and BE (3.24 vs. –0.86, p = 0.005). Depending on the lack or possibility of oral food intake, patients in the end jejunostomy group had different levels of the markers phosphate, Mg, Ca, urea, and creatinine, with all of these parameters within normal laboratory limits. When the end ileostomy group was divided into subgroups depending on the lack or possibility of oral food intake, differences in C-reactive protein activity were found (55.6 vs. 25.7, p = 0.041). Conclusions : Patients with an end jejunostomy syndrome are more prone to metabolic acidosis with significant alkali deficiencies.